Multiple Myeloma with Suspected Non-Secretory Type - Annisa Ginar Indrarsi; Usi Sukorini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Multiple Myeloma (MM) is a hematological malignancy characterized by clonal plasma cell in bone marrow that produce abnormal globulin, which resulted in monoclonal gammopathy. Multiple Myeloma Non-Secretory (MMNS) is a very rare form of multiple myeloma with monoclonal plasmocytic proliferation in bone marrow supported by clinical manifestation and radiological findings. However, plasma cells fail to secrete immunoglobulin. A 44-year-old female came to Sardjito General Hospital with main complaints of weakness and back pain. General weakness and pale palpebral conjunctiva were 6 observed (+/+), liver and spleen were not palpable. Blood test results were as follows: Hb 3.0 g/dL, RBC 1.07 x 10 / Î¼L, WBC 3 3 562 x 10 /Î¼L, PLT 114 x 10 /Î¼L, A/G ratio 1.07, BUN 51.5 mg/dL, creatinine 4.62 mg/dL, and calcium 3.1 mmol/L. Skeletal survey suggested a multiple osteolytic. Protein electrophoresis revealed hypogammaglobulinemia with no M-spike. There were 66% of plasma cells in bone marrow. Patient was diagnosed by MMNS. Diagnosis MMNS can be established if clonal plasmacytes is accompanied with renal insufficiency and hypercalcemia. However, monoclonal gammopathy was not found in serum protein electrophoresis. A case reported of 44-year-old female diagnosed as MMNS with 'punched out' multiple osteolytic, increased plasma cells in bone marrow without evidence of paraprotein in circulation proved by low A/G ratio and negative M-spike.